THE INFLUENCE OF COMPETENCE AND WORK EXPERIENCE ON THE QUALITY OF PERSONNEL PERFORMANCE IN THE MEDICAL AND HEALTH DIVISION OF THE LAMPUNG REGIONAL POLICE - Anggraini, Nova Mierlisa; Purnomo, Agus (Jurnal Riset Multidisiplin Edukasi, 2026)
Personnel performance is an important factor in supporting organizational goal achievement, particularly in police healthcare institutions that face complex job demands and responsibilities. Optimal performance is influenced by various factors, including competence and work experience. Adequate competence enables personnel to perform their duties professionally, effectively, and in accordance with applicable procedures and operational standards, while work experience develops practical abilities in decision-making, problem-solving, and adapting to diverse work situations. This study aims to analyze the effects of competence and work experience on personnel performance at the Medical and Health Affairs Division (Biddokkes) of the Lampung Regional Police using a quantitative approach and survey method. The findings indicate that competence has a positive and significant effect on personnel performance, suggesting that improvements in knowledge, skills, and professional capabilities contribute to better performance outcomes. Work experience also has a positive and significant effect, as personnel with broader experience tend to perform their duties more effectively, accurately, and professionally when dealing with various workplace situations. Furthermore, competence and work experience simultaneously have a positive and significant effect on personnel performance, indicating that the combination of strong competence and adequate work experience can contribute to optimal performance. Based on these findings, Biddokkes of the Lampung Regional Police should continuously develop personnel competence through technical training, advanced education, professional certification, and development programs aligned with job requirements. The organization should also provide broader opportunities for personnel to gain practical experience through job rotations, field assignments, and participation in various operational activities. These efforts are expected to enhance personnel capabilities in responding to diverse work situations, strengthen professionalism, and ultimately promote continuous improvements in the quality of personnel performance